PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KREATIVITAS DAN HASIL BELAJAR IPA KELAS V SEKOLAH DASAR - Kumala Dewi, Ririn Andriani; Fatkhiyani, Kiki; Indriyani, Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the difficulty of students in concentrating to understand the subject matter which results in a lack of development of creativity skills and student learning outcomes. The purpose of this study is to determine the influence of the project-based learning model on the creativity and learning outcomes of grade V students on the learning of food chain science. This research was conducted at SDN 1 Karangampel Kidul. The research method used is True Experimental Design in the form of Pretest-Posttest Control Group Design. This study used 2 sample groups, namely a control class of 45 people and an experimental class of 45 people. The experimental group is a group of students who are given the treatment of a project-based learning model, while the control group is a group of students who use a conventional model. The instruments used are test questions to determine learning outcomes and observation sheets to determine student creativity which is then carried out in experimental and control classes. As a result of this study, Mann Whitney's test on creativity observation is known to have an Asymp value. Sig. (2-tailed) of 0.006 so that Asymp. Sig. (2-tailed) is stated to be less than 0.05 (0.006 < 0.05), so it can be concluded that Ha is accepted or there is a difference in creativity between students in the experimental class and students in the control class. In the analysis of the Mann Whitney test, the students' learning outcomes were known to have Asymp scores. Sig. (2-tailed) by 0.000 so that Asymp. Sig. (2-tailed) is stated to be less than 0.05 (0.000 < 0.05), which can be interpreted as Ha accepted or there is a significant difference in science learning outcomes between students in the experimental class and students in the control class. Therefore, it can be concluded that there is an influence of the project-based learning model on the creativity and learning outcomes of grade V students on the learning of food chain science materials.